The Effect of Using the Surgical Mask on the Status of Cerebral Oxygen Saturation and End-Tidal Carbon Dioxide in Health Care Workers - Ghorbani, Jahangir; Safavi Naini, Ali; Jahangirifard, Alireza; Raad, Nasim; Karimi-Galougahi, Mahboobeh; Moradi, Alireza; Mirtajani, Seyed Bashir; Doulabi, Seied-Reza Seied-Mohammad (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: With the outbreak of the new coronavirus (SARS-COV-2), one of the challenges ahead has been to control the prevalence of the disease in the world. However, because the main way the virus enters the host is through the respiratory tract, the use of a mask is more necessary than in other cases. The medical staff who are in contact with these patients in closed environments in the operating room and other places are forced to use the mask continuously to prevent infection. Aim: Considering the necessity of using a mask in the prevalence of COVID 19, especially in the medical staff and the possible effects of this use on tissue oxygen and exhaled carbon dioxide, the present study investigates the effect of using a mask on health care. the present study investigates the effect of using a mask on health care. Methods: Twenty healthy members of the medical staff (staff working at Masih Daneshvari Hospital in Tehran) entered the study voluntarily according to the inclusion criteria. Everyone wore a mask for 2 hours a day. Brain oxygen delivery percentage was measured using cerebral oximetry and petCO2 with capnogram at 0, 60 and 180 minutes. Demographic information of participants about the age, sex and underlying diseases were also recorded in a pre-prepared questionnaire. Independent t-test, paired t-test and chi-square were used to compare the clinical features of the participants. P-value less than 0.05 was considered to show statistical significance. Results: The average of petCO2 in time 2 was significantly higher than time 1 and zero (P=0.001). Likewise, the average petCO2 factor at time one is significantly higher than at time zero. The relationship between BMI and changes in the studied indices shows that the left cerebral oxygenation factor, at times 0-60’ and 30’-60’ and also the right cerebral oxygenation factor at times 0’-60’, have a direct and significant relationship with BMI. Conclusion: Based on the results of the present study, it can be said that the use of surgical masks has significantly increased petCO2 in individuals, while the Pao2 index in some individuals has been associated with a downward trend.